Who's Up To the Challenge?82

Calculus Level 5

Define f ( x ) = x cos t t d t f(x)=\displaystyle\int_{x}^{\infty} \frac{\cos t}{t}dt

If the sum S = n = 1 f ( 2 π n ) S=\sum_{n=1}^{\infty}f(2\pi n) can be expressed as A γ B C D \frac{A\gamma}{B}-\frac{C}{D} for coprime positive integers A , B A,B and C , D C,D , find A + B + C + D A+B+C+D .

Notation : γ \gamma denotes the Euler-Macheroni constant .


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Syed Shahabudeen
Jan 24, 2019

On substituting x = t + 2 π n x=t+2\pi n ,(since we know c o s ( t + 2 π n ) = c o s ( t ) cos\left( t+2\pi n \right) =cos(t) )we can write f ( 2 π n ) = 2 π n c o s x x d x = 0 c o s ( t ) ( t + 2 π n ) d t f\left( 2\pi n \right) =\int _{ 2\pi n }^{ \infty }{ \frac { cosx }{ x } } dx=\int _{ 0 }^{ \infty }{ \frac { cos\left( t \right) }{ \left( t+2\pi n \right) } dt } we know that 0 c o s ( t ) ( t + 2 π n ) d t = 0 L { c o s ( t ) } L 1 { 1 t + 2 π n } d s = 0 ( s s 2 + 1 ) e 2 n π s d s \int _{ 0 }^{ \infty }{ \frac { cos\left( t \right) }{ \left( t+2\pi n \right) } dt } =\int _{ 0 }^{ \infty }{ L \left\{ cos(t) \right\} } { L }^{ -1 }\left\{ \frac { 1 }{ t+2\pi n } \right\} ds=\int _{ 0 }^{ \infty }{ \left( \frac { s }{ { s }^{ 2 }+1 } \right) { e }^{ -2n\pi s } } ds on substituting the integral representation of f ( 2 π n ) f\left( 2\pi n \right) into the summation we'll get n = 1 0 ( s s 2 + 1 ) e 2 n π s d s = 0 ( s s 2 + 1 ) n = 1 e 2 π n s d s \sum _{ n=1 }^{ \infty }{ \int _{ 0 }^{ \infty }{ \left( \frac { s }{ { s }^{ 2 }+1 } \right) { e }^{ -2n\pi s } } ds } =\int _{ 0 }^{ \infty }{ \left( \frac { s }{ { s }^{ 2 }+1 } \right) \sum _{ n=1 }^{ \infty }{ { e }^{ -2\pi ns }ds } } by applying infinite geometric series approach we can compute the following sum to be n = 1 e 2 π n s d s = 1 e 2 π s 1 { \sum _{ n=1 }^{ \infty }{ { e }^{ -2\pi ns }ds } =\frac { 1 }{ { e }^{ 2\pi s }-1 } } on rearranging the third equation of this solution part , we can write it as 0 s ( s 2 + 1 ) ( e 2 π s 1 ) d s = ψ ( 1 ) 2 1 4 \int _{ 0 }^{ \infty }{ \frac { s }{ \left( { s }^{ 2 }+1 \right) \left( { e }^{ 2\pi s }-1 \right) } } ds=\frac { -\psi \left( 1 \right) }{ 2 } -\frac { 1 }{ 4 } (binets second integral ) formula for digamma function) we know that ψ ( x ) = γ + n = 0 ( x 1 ) ( n + 1 ) ( n + x ) \psi \left( x \right) =-\gamma +\sum _{ n=0 }^{ \infty }{ \frac { \left( x-1 \right) }{ \left( n+1 \right) \left( n+x \right) } } therefore ψ ( 1 ) = γ \psi \left( 1 \right) =-\gamma and so our final result will be n = 1 f ( 2 π n ) = γ 2 1 4 \sum _{ n=1 }^{ \infty }{ f\left( 2\pi n \right) } =\frac { \gamma }{ 2 } -\frac { 1 }{ 4 }

Nice solution.......!!! I didn't know about Binet's second integral.......

Aaghaz Mahajan - 2 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...